2021
DOI: 10.3389/fnins.2021.781964
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke, Glucocorticoids, and Remote Hippocampal Damage: A Translational Outlook and Implications for Modeling

Abstract: Progress in treating ischemic stroke (IS) and its delayed consequences has been frustratingly slow due to the insufficient knowledge on the mechanism. One important factor, the hypothalamic-pituitary-adrenocortical (HPA) axis is mostly neglected despite the fact that both clinical data and the results from rodent models of IS show that glucocorticoids, the hormones of this stress axis, are involved in IS-induced brain dysfunction. Though increased cortisol in IS is regarded as a biomarker of higher mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…Ischemia-induced HPA activation which represents a quick physiological response, resulting in a prolonged increase in blood glucocorticoid levels, was described about 3 decades ago [ 20 , 21 , 22 ]. The fact that the stress response mediated by the HPA axis is associated with ischemic stroke has been confirmed in numerous further clinical and preclinical studies (see [ 8 ] for a review). A prolonged excess of glucocorticoids is believed to aggravate ischemic brain injury via the unwarranted activation of their receptors and increase the vulnerability of neurons in selected brain regions to neurodegeneration and demise.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ischemia-induced HPA activation which represents a quick physiological response, resulting in a prolonged increase in blood glucocorticoid levels, was described about 3 decades ago [ 20 , 21 , 22 ]. The fact that the stress response mediated by the HPA axis is associated with ischemic stroke has been confirmed in numerous further clinical and preclinical studies (see [ 8 ] for a review). A prolonged excess of glucocorticoids is believed to aggravate ischemic brain injury via the unwarranted activation of their receptors and increase the vulnerability of neurons in selected brain regions to neurodegeneration and demise.…”
Section: Discussionmentioning
confidence: 95%
“…One of the main reasons for this continuous failure may be due to problems with the validity of the models used [ 6 , 7 ]. Though the involvement of the stress and neurohumoral system in strokes is well-documented in clinical studies, it is still neglected in rodent models of ischemic stroke [ 8 ], although increased cortisol is associated with a worse outcome and the development of delayed cognitive deficits. Limbic structures, primarily the hippocampus, which coordinate both cognitive and emotional functions, have a high density of corticosteroid receptors, and this may be related to their selective vulnerability to stress factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, post-stroke hyperglycemia and hypokalemia may reflect the stress-related activation and a disorder of the hypothalamic–pituitary–adrenal (HPA) axis. HPA axis dysregulation believed to play a key role in the process of successive energy pump failure and various signaling cascades of IS 38 . In addition, a high cortisol level would activate the renin–angiotensin–aldosterone system (RAAS) to induce low serum potassium 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most treatment strategies currently followed that were developed by targeting known key pathogenetic links are often inadequately effective. The role of stress responses 38 and stress-related markers 3 has been proven to play a pivotal role in IS progression and has gained increasing attention. Our results suggested that comprehensive treatments including appropriate potassium supplementation, hypoglycemic treatment, and stress response blocker (β-blocker, RAAS inhibitor) may improve the short-term prognosis with high GPR levels.…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis dysfunction associated with stroke is generally neglected, though both clinical data and the results from rodent models of IS show that glucocorticoids are tightly involved in IS-induced brain dysfunction (see [ 34 ] for review). Adrenal glucocorticoid stress response in acute stroke is harmful.…”
Section: Discussionmentioning
confidence: 99%